Analisis Gaya Bahasa Dalam Novel Segi Tiga Karya Sapardi Djoko Damono - Azizah, Waviq; Erdayani, Rizki; Martius, Martius; Murny, Murny (Gurindam: Jurnal Bahasa dan Sastra, 2025)
This research is driven by high school literary learning exercises like evaluating novels, which frequently neglect to address or consider language style and diction. This study attempts to explain the linguistic styles found in Sapardi Djoko Damono's novel Segi Tiga. Techniques for listening and taking notes were used in the data collection process. The study's findings on language style included 278 data, of which 72 were in the simile style, 65 in the metaphorical style, 90 in the personfication type, 3 in the metonymic style, 3 in the synecdoche style, and the remaining 2 in the allegorical language style. 3 data, 11 data for hyperbolic language, 17 data for repetition, 6 data for ironic language, and idiom language.